ORIENTASI PEMILIH PEREMPUAN TERHADAP CALON LEGISLATIF PEREMPUAN DI DAPIL VI PADA PEMILIHAN UMUM DPRD KOTA PEKANBARU TAHUN 2019 - Latiffa Harisa; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The orientation of female voters towards female legislative candidates in electoral district VI in the 2019 Pekanbaru City DPRD general election is interesting to study. The low orientation of female voters towards female legislative candidates as well as the factors that influence the low orientation of female voters towards female legislative candidates here is voter orientation, which is the ability of voters to express their own identity and that of those around them. Women voters with voting votes often become a bone of contention in every general election (Election). In addition to being large in number, women's votes are often used as a benchmark for male voters and first-time voters. This more dominant voice is expected by each of the respective prospective candidates in election participation. This study uses the theory of Prof. Mariam Budiarjo (2008; 136) which categorizes voter behavior into two dimensions, namely rational voter behavior and emotional voter behavior. General Election of Pekanbaru City DPRD in 2019. The research location was carried out in Pekanbaru City, to be precise in Dapil VI of Senapelan and Payung Sekaki Districts. Furthermore, data collection techniques were carried out by interviews and documentation. This research use desciptive qualitative approach. The results of this study are the low orientation of female voters towards female legislative candidates in Dapil VI in the 2019 Pekanbaru City DPRD general election due to voter distrust in choosing female legislative candidates with the notion that female leaders make decisions using emotional rather than rational means. Keyword : Orientation of Female Voters Towards Womana Legislative Candidates in Electoral Districts VI in 2019 Pekanbaru City DPRD General Election